KARAKTERISASI CAP ROCK DAN RESERVOIR AREA GEOTERMAL X BERDASARKAN STUDI SEISMISITAS DENGAN METODE SED - Anjar Oktikawati; Udi Harmoko; Imam Baru Raharjo (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2013)
X geothermal area is located in the western Indonesia with high seismicity. Microearthquake (MEQ) data in geothermal exploration usually used as one of tools for approximating permeable structure in geothermal reservoirand for determining boundaries of reservoir.Five seismic recording stations recorded the earthquake in the period October 2011 to December 2011. From 34671 records data stored on the period, only 68 events microearthquake (MEQ) are inverted to obtain the hypocenter with Single Event Determination method (SED).Result inversion of the method show that permeable zone at X geothermal area is located at 10000 to 22000 X axis and 5000 to 12000 Y axis. Depth distribution shows that cap rock is located about 580 meter to 1100 meter mean sea level and the reservoir is located at altitude about 600 meter to -2000 depth. Keywords: microearthquake (MEQ), hypocenter, SED, reservoir geothe.